2003
DOI: 10.1016/s1062-1458(03)00194-6
|View full text |Cite
|
Sign up to set email alerts
|

Early and late effects of clopidogrel in patients with acute coronary syndromes

Abstract: Background-The risk of ischemic events is high, both early and late after acute coronary syndromes (ACS). We examine the benefits and risks associated with the use of adding clopidogrel to aspirin within the first 30 days and later (31 days to 12 months) in 12 562 patients with ACS. Methods and Results-A total of 12 562 ACS patients were randomized to receive clopidogrel (300 mg initially followed by 75 mg/d) or placebo for 3 to 12 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
65
0
5

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(73 citation statements)
references
References 5 publications
3
65
0
5
Order By: Relevance
“…1,14,15 Therefore, inhibition of platelet aggregation is believed to be crucial for the strategic management of primary and secondary prevention of thromboembolic events in high-risk patients. 1,[15][16][17] One important finding of the present study was that the CD62p expression was substantially higher pre-procedure in the study patients than in the normal control subjects, which is important information for the management of patients with ACS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,14,15 Therefore, inhibition of platelet aggregation is believed to be crucial for the strategic management of primary and secondary prevention of thromboembolic events in high-risk patients. 1,[15][16][17] One important finding of the present study was that the CD62p expression was substantially higher pre-procedure in the study patients than in the normal control subjects, which is important information for the management of patients with ACS.…”
Section: Discussionmentioning
confidence: 99%
“…Previous clinical trials showed that early use of potent anti-platelet agents gave most clinical benefit to patients with ACS; 16,17 however, the efficacy of these anti-platelet therapies for secondary prevention following ACS was not based on measuring platelet activity in individual patients, but rather on clinical observation. 1,2,5,16,17 Therefore, the findings of the present study are clinically important because they reinforce the rationale of strategic management based on the finding of the previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Combining our findings with those of the other studies 5,8,10,15 supports the suggestion that early administration of antiplatelet agents and IIb/IIIa receptor inhibitors could provide additional benefit to patients with ACS. 3,6,7,16 Correlation Between Platelet Activity and Myocardial Damage Notably, while the relationship between the thromboembolic risk and platelet activity has been extensively debated, 1,2,[5][6][7][8][9]14 the association between myocardial damage and platelet activation has seldom been studied. 10 Plaque rupture, an index of acute inflammatory stimulus, increases platelet activation 11 and additionally, acute ischemic stroke or AMI, which indicates tissue necrosis, markedly enhances platelet activity.…”
Section: Platelet Activity Is An Index Of a Thromboembolic Eventmentioning
confidence: 99%
“…A reduction of recurrent ischemia was already present within 6 h of randomization. 30 The salutary effects were noted across all of the subgroups, including those without ST-segment deviation or troponin release and those with a low TIMI risk score. 14,17 The major benefit was a reduction in MI; although death and stroke trended in favor of clopidogrel, the reduction in these events did not achieve statistical significance.…”
Section: Clopidogrelmentioning
confidence: 92%